A method for preparing internally cured cementitious materials with in-situ generated organic-inorganic core-shell structures
Patent Information
- Application Number
- CN202410482509.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-22
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-04-22
AI Technical Summary
然而,研究发现,在HPC/UHPC中掺加SAP实现内养护时,虽然储存于SAP中的部分内养护水可通过扩散与水泥反应,但水泥水化产物无法在SAP占据空间生长堆积,最终SAP颗粒产生干燥坍陷,形成与原占据体积基本相同的有害大孔,因而成为硬化HPC/UHPC中的薄弱环节
[0013]本发明可选用各种市场上获得的超吸水树脂,要求超吸水树脂的颗粒大小可通过30~400目的筛孔。与现有技术相比,在HPC/UHPC等高性能水泥基材料中使用本发明所述的表面纳米改性超吸水树脂作为内养护材料,制备可原位生成有机-无机核壳结构的内养护水泥基材料,其有益效果主要体现在,对超吸水树脂进行表面纳米改性和隔离处理,并在水泥基材料中掺加后,可在水泥水化硬化过程中原位形成有机-无机核壳结构,其中在超吸水树脂内部吸入的自由水对HPC/UHPC发挥内养护作用,以减小自收缩,形成的有机-无机核壳结构对硬化水泥基材料具有明显的增强作用,从而制备得到可原位生成有机-无机核壳结构的内养护水泥基材料。
Smart Images

Figure CN118373644B_ABST
Abstract
Description
(I) Technical Field
[0001] This invention relates to a method for preparing an in-situ organic-inorganic core-shell structured internal curing cement-based material, belonging to the technical field of cement concrete materials. (II) Background Technology
[0002] With the development of concrete technology, high-performance concrete (HPC) and ultra-high-performance concrete (UHPC), which aim for high and ultra-high strength and durability, have been increasingly widely used in engineering. However, HPC / UHPC, characterized by low water-cement ratio and high cementitious material content, suffers from large early-stage autogenous shrinkage deformation. If not properly addressed, microcracks can easily form on the HPC / UHPC surface. - Corrosive ions can easily penetrate along microcracks, leading to a significant decrease in the durability and service life of ultra-high performance concrete structures. Therefore, how to take appropriate technical measures to effectively reduce autogenous shrinkage and prevent shrinkage cracking is the core issue in effectively improving the durability and service life of marine ultra-high performance concrete structures.
[0003] To reduce autogenous shrinkage, superabsorbent polymers (SAPs) are commonly incorporated into HPC / UHPCs both domestically and internationally. SAPs' extremely high water absorption and rehydration properties reduce the degree of self-drying during cement hydration, effectively minimizing autogenous shrinkage and preventing early shrinkage cracking. However, research has found that while some of the internal curing water stored in SAP can react with cement through diffusion when adding SAP to HPC / UHPCs for internal curing, cement hydration products cannot grow and accumulate in the spaces occupied by SAPs. Ultimately, the SAP particles dry and collapse, forming harmful macropores with a volume essentially the same as their original size, thus becoming a weak point in the hardened HPC / UHPC. Clearly, these pores negatively impact the mechanical properties and durability properties of hardened HPC / UHPCs, such as resistance to chloride ion penetration. Although the internal curing effect of SAP can reduce the tendency to crack due to autogenous shrinkage and increase the degree of cement hydration, and by controlling the amount of additional water introduced, the decrease in mechanical properties and durability of hardened HPC / UHPC caused by the macropores formed by SAP can also be effectively compensated, the characteristic of SAP forming collapsed macropores due to water loss is not eliminated, and its adverse effect on the performance of hardened HPC / UHPC cannot be ignored. If an organic-inorganic core-shell structure with a certain strength can be formed in situ in HPC / UHPC, the decrease in strength of hardened HPC / UHPC caused by the drying collapse of SAP can be compensated to some extent. (III) Summary of the Invention
[0004] To address the aforementioned problems, the main objective of this invention is to provide a method for preparing an in-situ organic-inorganic core-shell structured internal curing cement-based material.
[0005] The technical solution adopted in this invention is:
[0006] A method for preparing an in-situ organic-inorganic core-shell structured internally cured cementitious material includes the following steps: Step 1: Adding superabsorbent resin particles to a silica sol with a mass concentration of 10%–30%, performing water absorption treatment for 0.5–5 hours, and then filtering off the liquid using a 100–250 mesh filter to obtain a surface-modified superabsorbent resin; the mass ratio of the superabsorbent resin to the silica sol is 1:500–2000; Step 2: Adding the surface-modified superabsorbent resin to water according to the required proportion designed by the mixing ratio. Simultaneously, a high-performance water-reducing agent is added and stirred for 0.5–1 min to prepare a surface-modified superabsorbent resin dispersion; Step 3: The cement and mineral admixtures required by the mix design are stirred for 0.5–1 min. After stirring evenly, the surface-modified superabsorbent resin dispersion is added and stirring is continued for 0.5–1.0 min to prepare a cement slurry with surface-modified superabsorbent resin; Step 4: The sand, stone, and fiber materials required by the mix design are added to the cement slurry in sequence and stirring is continued for 1–5 min to prepare an in-situ organic-inorganic core-shell structure internal curing cement-based material.
[0007] Furthermore, the fineness of the superabsorbent resin particles is 30 mesh to 400 mesh.
[0008] Furthermore, the pH value of the silica sol is 7.0 to 11.0.
[0009] Furthermore, the pH value of the silica sol is 1.5 to 4.8.
[0010] A method for preparing an in-situ organic-inorganic core-shell structured internally cured cementitious material, comprising the following steps: Step 1: Adding superabsorbent resin particles to silica sol and performing water absorption treatment for 0.5h to 5h, then filtering off the liquid using a 100-250 mesh filter to obtain a surface-modified superabsorbent resin; Step 2: Adding a separating material to the surface-modified superabsorbent resin and stirring for 0.5-1.5min to obtain a surface-modified superabsorbent resin after separation treatment; Step 3: Adding the surface-modified superabsorbent resin after separation treatment to... Step 4: Add the required amount of water according to the mix design, and simultaneously add a high-performance water-reducing agent. Stir for 0.5–1 min to prepare a surface-modified superabsorbent resin dispersion. Step 5: Add the required amount of cement and mineral admixtures according to the mix design for 0.5–1 min. After stirring evenly, add the surface-modified superabsorbent resin dispersion and continue stirring for 0.5–1.0 min to prepare a cement slurry with surface-modified superabsorbent resin. Step 6: Add the required amount of sand, stone, and fiber materials according to the mix design to the cement slurry in sequence and continue stirring for 1–5 min to prepare an in-situ organic-inorganic core-shell structure internal curing cement-based material.
[0011] Furthermore, the isolation material is one or a mixture of two or more of the following: fly ash, silica fume, or slag powder.
[0012] Furthermore, the mass ratio of the insulating material to the superabsorbent resin is 6 to 20:1.
[0013] This invention can utilize various commercially available superabsorbent resins, requiring the superabsorbent resin particle size to pass through a 30-400 mesh sieve. Compared with existing technologies, using the surface-modified superabsorbent resin described in this invention as an internal curing material in high-performance cement-based materials such as HPC / UHPC allows for the preparation of internally cured cement-based materials with an in-situ organic-inorganic core-shell structure. The beneficial effects are mainly reflected in the fact that after surface nano-modification and isolation treatment of the superabsorbent resin, and its addition to cement-based materials, an organic-inorganic core-shell structure can be formed in-situ during the cement hydration and hardening process. The free water absorbed inside the superabsorbent resin plays an internal curing role for HPC / UHPC, reducing self-shrinkage. The formed organic-inorganic core-shell structure has a significant reinforcing effect on the hardened cement-based material, thus preparing an internally cured cement-based material with an in-situ organic-inorganic core-shell structure. (iv) Description of the attached drawings
[0014] Figure 1 The images are obtained by scanning electron microscopy from the dried samples of superabsorbent resin prepared in Comparative Example 1 and Example 1, respectively, without and with surface nano-modification. Figure 2The images are scanning electron microscope (SEM) images of the cement-based materials prepared in Comparative Example 1 and Example 1 after 28 days of curing. (V) Detailed Implementation
[0015] The present invention will be further described below with reference to specific embodiments, but the scope of protection of the present invention is not limited thereto.
[0016] Example 1:
[0017] Commercially available superabsorbent polymer (SAP) with a particle size of 30-60 mesh was used as the raw material for preparing in-situ organic-inorganic core-shell structured internal curing cementitious materials. The water absorption ratio in tap water was measured to be 327.6 g / g SAP using the tea bag method. SAP particles were weighed and added to a 30% silica sol solution for water absorption treatment. The mass ratio of SAP to silica sol was 1:2000, and the pH of the silica sol was 8.8. After 1 hour of water absorption, the liquid was filtered out using a 100-mesh filter to prepare the surface-modified superabsorbent polymer. Its liquid absorption rate was measured to be 57.8 g / g SAP, and the amount of adsorbed nano-silica on the surface was determined to be 5.0 g / g SAP using the weight loss on ignition method.
[0018] Scanning electron microscopy (SEM) images of the dried samples of superabsorbent resins prepared in Comparative Example 1 and Example 1, without and with surface nano-modification, are shown below. Figure 1 As shown, after surface nano-modification and drying, a layer of nano-silica is formed on the surface of the superabsorbent resin.
[0019] The prepared surface-modified superabsorbent resin was used to prepare cement paste according to the cement paste mix proportions in Table 1. After curing for 28 days, samples were taken for scanning electron microscopy (SEM) testing. The SEM images obtained in Comparative Example 1 and Example 1 are shown below. Figure 2 As shown. By Figure 2 It is evident that when unmodified superabsorbent resin is added to cement paste, the resulting collapsed macropores lack a hard shell structure. However, when the surface-modified superabsorbent resin prepared in Example 1 is added to cement paste, a core-shell structure is formed in situ during the hydration and hardening process. This hard shell layer is a CSH gel layer formed by the reaction of nano-silica and calcium hydroxide, a cement hydration product, which can enhance the hardened cement-based material.
[0020] Table 1
[0021]
[0022] To verify the reinforcing effect of the core-shell structure on the internal curing cementitious material, the mortar mix proportions shown in Table 2 were designed. The cement used was 52.5 grade white cement, the sand was 28-40 mesh quartz sand, and the water-reducing agent was polycarboxylate high-performance water-reducing agent with a mass concentration of 20%. The preparation method of the in-situ organic-inorganic core-shell structure internal curing cementitious material includes the following steps:
[0023] Step 1: Weigh 1.02g of superabsorbent resin particles and add them to a 30% silica sol solution for water absorption treatment. After 1 hour of water absorption, filter out the liquid through a 100-mesh filter to prepare a surface-modified superabsorbent resin. The mass ratio of superabsorbent resin particles to silica sol is 1:2000, and the pH value of the silica sol is 8.8.
[0024] Step 2: Add the prepared surface nano-modified superabsorbent resin to 162ml of water and add 1.62g of polycarboxylate high-performance water-reducing agent. Stir for 0.5min to prepare a dispersion of surface nano-modified superabsorbent resin.
[0025] Step 3: Add the surface nano-modified superabsorbent resin dispersion to 540g of cement and stir for 1.0min to prepare cement slurry with surface nano-modified superabsorbent resin.
[0026] Step 4: Add 1350g of sand to the cement slurry containing surface-modified superabsorbent resin, and continue stirring for 2 minutes to prepare an in-situ organic-inorganic core-shell structured internally cured cement-based material. Mold 40mm×40mm×160mm mortar specimens and perform strength testing according to GB / T17671-1999 "Test Method for Strength of Cement Mortar (ISO Method)". The test results are shown in Table 2. As can be seen from Table 2, although the amount of surface-modified superabsorbent resin is relatively large, the strength of the prepared cement mortar is still significantly higher, indicating that the in-situ formed organic-inorganic core-shell structure helps to improve the strength of the hardened cement-based material.
[0027] Table 2
[0028]
[0029] Examples 2-5:
[0030] Commercially available superabsorbent polymer (SAP) with a particle size of 30–60 mesh was used as the raw material for preparing superabsorbent polymers that form an organic-inorganic core-shell structure in situ within cement-based materials. The water absorption ratio in tap water was measured to be 327.6 g / g SAP using the tea bag method. SAP particles were weighed and added to silica sol solutions with mass concentrations of 10%, 15%, 20%, and 25% for water absorption treatment. The mass ratio of SAP to silica sol was 1:2000, and the pH of the silica sol was 8.8. After 1 hour of water absorption, the liquid was filtered out using a 100-mesh filter to prepare the surface-modified superabsorbent polymer. The liquid absorption rate and the amount of nano-silica adsorbed on the surface are shown in Table 3.
[0031] Table 3
[0032]
[0033] The mortar mix proportions used in Examples 2 to 5 are shown in Table 4. The cement used is PW52.5 white cement, the sand is 28-40 mesh quartz sand, and the water-reducing agent is polycarboxylate high-performance water-reducing agent with a mass concentration of 20%. The preparation method of the in-situ generated organic-inorganic core-shell structure internal curing cementitious material includes the following steps:
[0034] Step 1: Weigh 0.286g, 0.372g, 0.545g, and 0.691g of superabsorbent resin particles respectively, and add them to silica sol with mass concentrations of 10%, 15%, 20%, and 25% for water absorption treatment. After water absorption for 1 hour, filter out the liquid through a 100-mesh filter to prepare surface nano-modified superabsorbent resin. The mass ratio of superabsorbent resin particles to silica sol is 1:2000, and the pH value of the silica sol is 8.8.
[0035] Step 2: Add 162ml of water containing 1.62g of polycarboxylate superabsorbent agent to the surface nano-modified superabsorbent resin prepared in Step 1, and stir for 1min to obtain a surface nano-modified superabsorbent resin dispersion.
[0036] Step 3: Add the above-mentioned surface nano-modified superabsorbent resin dispersion to 540g of cement and stir for 1.0min to prepare cement slurry with surface nano-modified superabsorbent resin.
[0037] Step 4: Add 1350g of quartz sand to the cement slurry containing surface-modified nano-superabsorbent resin, and continue stirring for 1.5min, 1min, 1.5min, and 2min respectively to prepare an in-situ organic-inorganic core-shell structured internally cured cement-based material. Mold 40mm×40mm×160mm mortar specimens and test their strength according to GB / T17671-1999 "Test Method for Strength of Cement Mortar (ISO Method)". The test results are shown in Table 4. As can be seen from Table 4, although the amount of surface-modified nano-superabsorbent resin is relatively large, the strength of the prepared cement mortar is still significantly higher, indicating that the in-situ formed hard shell structure helps to improve the strength of the hardened cement-based material.
[0038] Table 4
[0039]
[0040] Examples 6-8:
[0041] Commercially available superabsorbent polymer (SAP) with a particle size of 100–200 mesh was used as the raw material for preparing surface-modified superabsorbent polymer. The water absorption ratio in tap water was measured to be 293.5 g / gSAP using the tea bag method. SAP particles were weighed and added to a 20% silica sol solution for water absorption treatment. The mass ratio of SAP particles to silica sol was 1:500, 1:1000, and 1:1500, respectively. The pH of the silica sol was 7.0. After 3 hours of water absorption, the liquid was filtered out using a 150-mesh filter to prepare the surface-modified superabsorbent polymer. The liquid absorption rate and the amount of nano-silica adsorbed on the surface are shown in Table 5.
[0042] Table 5
[0043]
[0044] The mortar mix proportions used in Examples 6 to 8 are shown in Table 6. The cement used is PW52.5 white cement, the sand is 28-40 mesh quartz sand, and the water-reducing agent is polycarboxylate high-performance water-reducing agent with a mass concentration of 20%. The preparation method of the in-situ generated organic-inorganic core-shell structure internal curing cementitious material includes the following steps:
[0045] Step 1: Weigh 0.594g, 0.491g, and 0.437g of superabsorbent resin particles respectively, and add them to a 20% silica sol solution for water absorption treatment. After 3 hours of water absorption, filter out the liquid through a 150-mesh filter to prepare surface-modified superabsorbent resin. The mass ratio of superabsorbent resin particles to silica sol is 1:500, 1:1000, and 1:1500, respectively, and the pH value of the silica sol is 7.0.
[0046] Step 2: Add 1.62g of polycarboxylate superplasticizer to 162ml of water respectively, and stir for 1min to prepare a surface nano-modified superabsorbent resin dispersion.
[0047] Step 3: Add the above-mentioned surface nano-modified superabsorbent resin dispersion to 540g of cement and stir for 0.8min to prepare cement slurry with surface nano-modified superabsorbent resin.
[0048] Step 4: Add 1350g of quartz sand to the cement slurry containing surface-modified nano-superabsorbent resin, and continue stirring for 1min, 1.5min, and 2min respectively to prepare an in-situ organic-inorganic core-shell structured internally cured cement-based material. Mold 40mm×40mm×160mm mortar specimens and test their strength according to GB / T17671-1999 "Test Method for Strength of Cement Mortar (ISO Method)". The test results are shown in Table 6. As can be seen from Table 6, although the amount of surface-modified nano-superabsorbent resin is relatively large, the strength of the prepared cement mortar is still significantly higher, indicating that the in-situ formed hard shell structure helps to improve the strength of the hardened cement-based material.
[0049] Table 6
[0050]
[0051] Examples 9-15:
[0052] Commercially available superabsorbent polymer (SAP) with a particle size of 500–800 mesh was used as the raw material for preparing surface-modified superabsorbent polymer. The water absorption ratio in tap water was measured to be 343.6 g / gSAP using the tea bag method. SAP particles were weighed and added to silica sol solutions with a mass concentration of 20% for water absorption treatment. The mass ratio of SAP to silica sol was 1:1500, and the pH values of the silica sol were 1.5, 2.5, 3.5, 4.8, 9.0, 10.0, and 11.0, respectively. After 5 hours of water absorption, the liquid was filtered out using a 250-mesh filter to prepare the surface-modified superabsorbent polymer. The liquid absorption rate and the amount of nano-silica adsorbed on the surface are shown in Table 7.
[0053] Table 7
[0054]
[0055] The mortar mix proportions used in Examples 9 to 15 are shown in Table 6. The cement used is PW52.5 white cement, the sand is 28-40 mesh quartz sand, and the water-reducing agent is polycarboxylate high-performance water-reducing agent with a mass concentration of 20%. The preparation method of the in-situ generated organic-inorganic core-shell structure internal curing cementitious material includes the following steps:
[0056] Step 1: Weigh out 0.54g, 0.502g, 0.578g, 0.594g, 0.448g, 0.416g, and 0.475g of superabsorbent resin particles respectively, and add them to a 20% silica sol solution for water absorption treatment. After 5 hours of water absorption, filter out the liquid through a 250-mesh filter to prepare surface-modified superabsorbent resin. The mass ratio of superabsorbent resin particles to silica sol is 1:1500, and the pH values of the silica sol are 1.5, 2.5, 3.5, 4.8, 9.0, 10.0, and 11.0, respectively.
[0057] Step 2: Add the surface nano-modified superabsorbent resin prepared in Step 1 to 162ml of water containing 1.62g of polycarboxylate superplasticizer, and stir for 1min to prepare a dispersion of surface nano-modified superabsorbent resin.
[0058] Step 3: Add the above-mentioned surface nano-modified superabsorbent resin dispersion to 540g of cement and stir for 1min to prepare cement slurry with surface nano-modified superabsorbent resin.
[0059] Step 4: Add 1350g of quartz sand to the cement slurry containing surface-modified nano-superabsorbent resin, and continue stirring for 1.5min to prepare an in-situ organic-inorganic core-shell structured internally cured cementitious material. Mold 40mm×40mm×160mm mortar specimens and test their strength according to GB / T17671-1999 "Test Method for Strength of Cement Mortar (ISO Method)". The test results are shown in Table 8. As can be seen from Table 8, although the amount of surface-modified nano-superabsorbent resin is relatively large, the strength of the prepared cement mortar is still significantly higher, indicating that the in-situ formed hard shell structure helps to improve the strength of the hardened cementitious material.
[0060] Table 8
[0061]
[0062] Examples 16-18:
[0063] The preparation methods of the surface nano-modified superabsorbent resins in Examples 16-18 are the same as those in Examples 6-8.
[0064] Based on Examples 6-8, fly ash, silica fume, and slag powder were used as isolation materials, respectively. All fly ash, silica fume, and slag powder were sourced from Zhejiang Huwei Building Materials Group Co., Ltd.
[0065] The mix proportions of the cement-based materials used in Examples 16 to 18 are shown in Table 9. The cement used was 52.5 ordinary cement, the sand was natural medium sand with a fineness modulus of 2.84, and the coarse aggregate was natural crushed stone with a particle size of 5–20 mm. The water-reducing agent used was polycarboxylate high-performance water-reducing agent, with fly ash and slag added as mineral admixtures. 20 L of concrete mixture was prepared for each example.
[0066] Step 1: Weigh 11g, 9.1g, and 8.1g of superabsorbent resin particles respectively, and prepare surface-modified superabsorbent resins according to Examples 6-8 respectively; Step 2: Add fly ash, silica powder, and slag powder as isolation materials respectively. The amounts of fly ash, silica powder, and slag powder are 20 times, 10 times, and 15 times the amount of superabsorbent resin, respectively, which are 220g, 91g, and 121.5g, respectively. Stir for 0.5min, 1min, and 1.5min respectively to prepare surface-modified superabsorbent resins after isolation treatment; Step 3: Add the prepared surface-modified superabsorbent resins after isolation treatment to 3kg of water containing 30g of high-performance polycarboxylate superplasticizer, and stir for 0.75min respectively to prepare... A surface-modified superabsorbent resin dispersion was obtained. Step four: Weigh three portions of cementitious material, each containing 5 kg of cement, 2.5 kg of fly ash, and 2.5 kg of slag powder. Add each portion of cementitious material to a concrete mixer and stir for 1 min. Then add the aforementioned surface-modified superabsorbent resin dispersion to each portion and stir for 1 min to prepare a cement paste containing surface-modified superabsorbent resin. Step five: Add 16 kg of natural medium sand and 19 kg of crushed stone to the cement paste containing surface-modified superabsorbent resin, and continue stirring for 1 min, 1.5 min, and 2 min respectively to prepare an in-situ organic-inorganic core-shell structure internally cured cement-based material (high-performance concrete). 100 mm × 100 mm × 100 mm concrete specimens were formed and cured for 28 days. The results are shown in Table 9. As shown in Table 9, although the amount of superabsorbent resin after surface nano-modification and isolation treatment is relatively large, the strength of the prepared high-performance concrete is still significantly higher, indicating that the in-situ formed hard shell structure helps to improve the strength of hardened high-performance concrete.
[0067] Table 9
[0068]
[0069] Examples 19-25:
[0070] Step 1: The preparation method of the surface nano-modified superabsorbent resin in Examples 19-25 is the same as that in Examples 9-15.
[0071] Step 2: Add isolation material to the surface nano-modified superabsorbent resin and stir to prepare the surface modified superabsorbent resin after isolation treatment; wherein the isolation material is a mixture of two or three of the following: fly ash, silica powder and slag powder. The types and proportions of isolation materials used in each embodiment, as well as the proportions of the isolation materials to the superabsorbent resin and the stirring time, are shown in Table 10. The fly ash, silica powder and slag powder used are all from Zhejiang Huwei Building Materials Group Co., Ltd.
[0072] Table 10
[0073]
[0074] Step 3: The prepared surface-modified superabsorbent resin after isolation treatment is added to water containing high-performance polycarboxylate superplasticizer and stirred for 0.5 min to prepare a surface nano-modified superabsorbent resin dispersion; wherein, the water, superabsorbent resin dosage and superplasticizer dosage in each embodiment are shown in Table 11.
[0075] Step 4: Stir the cement and mineral admixtures required by the mix design for 1 minute. After stirring evenly, add the surface nano-modified superabsorbent resin dispersion and continue stirring for 1 minute to prepare the cement paste with surface nano-modified superabsorbent resin.
[0076] Step 5: Add the required sand, stone, and fiber materials according to the mix design to the cement paste in sequence, and continue stirring for 5 minutes to prepare the in-situ organic-inorganic core-shell structure internal curing cement-based material.
[0077] In steps three through five, the proportions of each component in each embodiment are shown in Table 11. The cement used was 52.5 ordinary cement, the sand was natural medium sand with a fineness modulus of 2.84, and the coarse aggregate was natural crushed stone with a particle size of 5–10 mm. Fly ash, slag, and silica fume were added as mineral admixtures, all sourced from Zhejiang Huwei Building Materials Group Co., Ltd. Steel fibers were added as reinforcing materials; the steel fibers used were straight, copper-plated microfibers purchased from Jiaxing Jingwei Steel Fiber Co., Ltd. 20 L of ultra-high performance concrete mixture was prepared in each embodiment. 100 mm × 100 mm × 100 mm concrete specimens were formed, cured for 28 days, and their strength was measured. The results are shown in Table 11. As can be seen from Table 11, although the amount of superabsorbent resin after surface nano-modification and isolation treatment was relatively large, the strength of the prepared ultra-high performance concrete was still significantly higher, indicating that the in-situ formed organic-inorganic core-shell structure helps to improve the strength of the hardened ultra-high performance concrete.
[0078] Table 11
[0079]
[0080] The above description of the embodiments is provided to enable those skilled in the art to understand and apply the present invention. It will be apparent to those skilled in the art that various modifications can be easily made to these embodiments, and the general principles described herein can be applied to other embodiments without creative effort. Therefore, the present invention is not limited to the embodiments described herein, and any improvements and modifications made to the present invention by those skilled in the art based on the disclosure thereof should be within the scope of protection of the present invention.
Claims
1. A method for preparing an in-situ organic-inorganic core-shell structured internal curing cementitious material, characterized in that, Includes the following steps: Step 1: Add superabsorbent resin particles to a silica sol with a mass concentration of 10%~30%, perform water absorption treatment for 0.5h~5h, and then filter out the liquid through a 100~250 mesh filter to prepare a surface-modified superabsorbent resin; the mass ratio of the superabsorbent resin particles to the silica sol is 1:500~2000; the pH value of the silica sol is 1.5~4.8; Step 2: Add an isolation material to the surface nano-modified superabsorbent resin and stir for 0.5~1.5 min to prepare the surface nano-modified superabsorbent resin after isolation treatment; The separating material is one or a mixture of two or more of fly ash, silica fume or slag powder; the mass ratio of the separating material to the superabsorbent resin is 6 to 20:
1. Step 3: Add the isolated surface nano-modified superabsorbent resin to the water required by the formula design in proportion, and add a high-performance water-reducing agent at the same time. Stir for 0.5~1 min to prepare a surface nano-modified superabsorbent resin dispersion. Step 4: Stir the cement and mineral admixtures required by the mix design for 0.5~1 min. After stirring evenly, add the surface nano-modified superabsorbent resin dispersion and continue stirring for 0.5~1.0 min to prepare cement paste with surface nano-modified superabsorbent resin. Step 5: Add the required sand, stone, and fiber materials according to the mix design to the cement paste in sequence, and continue stirring for 1-5 minutes to prepare the in-situ organic-inorganic core-shell structure internal curing cement-based material.
2. The method for preparing in-situ organic-inorganic core-shell structured internal curing cementitious material according to claim 1, characterized in that, The superabsorbent resin particles have a fineness of 30 mesh to 400 mesh.
Citation Information
Patent Citations
High-ductility white cement-based rapid sealing spraying material and preparation method thereof
CN115650671A